2018
DOI: 10.1038/s41395-018-0044-5
|View full text |Cite
|
Sign up to set email alerts
|

Lack of improvement of impaired chemical clearance characterizes PPI-refractory reflux-related heartburn

Abstract: Lack of improvement of impaired chemical clearance is a major determinant of PPI refractoriness. Timely post-reflux salivary swallowing represents a key defensive mechanism and a potential target for future treatment modalities in PPI-refractory reflux-related heartburn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 27 publications
3
64
0
Order By: Relevance
“…Previous multicenter studies have shown that PSPW index and MNBI can increase our ability to diagnose GERD . What's more, low PSPW index and low MNBI are demonstrated to independently predict response to PPI therapy and antireflux therapy in GERD . The reason why inconclusive GERD patients with low PSPW index or low MNBI only had partial response to PPI treatment may be partly due to inappropriate threshold of these two metrics to define GERD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous multicenter studies have shown that PSPW index and MNBI can increase our ability to diagnose GERD . What's more, low PSPW index and low MNBI are demonstrated to independently predict response to PPI therapy and antireflux therapy in GERD . The reason why inconclusive GERD patients with low PSPW index or low MNBI only had partial response to PPI treatment may be partly due to inappropriate threshold of these two metrics to define GERD.…”
Section: Discussionmentioning
confidence: 99%
“…PSPW can be identified on pH‐impedance monitoring as a distally migrating sequential impedance drop following a reflux episode, reaching the distal esophagus (Figure B) . PSPW index, the ratio of the PSPW count to number of reflux episodes, records the efficiency of chemical clearance and predicts reflux‐related heartburn responsive to PPIs . The relationship of PSPW to contraction reserve deserves further study, as reflux‐induced primary peristalsis, and potentially, RACs on FLIP topography will be influenced by the integrity of esophageal neural connections and smooth muscle function, which is the basis for contraction reserve.…”
Section: Supplementary Investigationmentioning
confidence: 99%
“…PSPW index, the ratio of the PSPW count to number of reflux episodes,77 records the efficiency of chemical clearance and predicts reflux-related heartburn responsive to PPIs 78,79. The relationship of PSPW to contraction reserve deserves further study, as reflux-induced primary peristalsis,F I G U R E 4 Adjunctive evaluation of esophageal peristaltic performance using novel metrics and techniques.…”
mentioning
confidence: 99%
“…Adults (age > 18 years) referred for esophageal physiologic testing for persisting typical and atypical reflux symptoms despite doubledose acid-suppressive therapy for at least 8 weeks at five centers (4 in Europe and one in the United States) were eligible for inclusion in this retrospective observational cohort study. Patients were included if alternate esophageal mechanisms for symptoms had been excluded with endoscopy, if they underwent ambulatory pH-impedance studies off acid-suppressive therapy, and if 10 acceptable supine water swallows were available for HRM analysis using Chicago Classification version 3.0 (CCv3.0).…”
Section: Me Thodsmentioning
confidence: 99%
“…1 An increase in frequency, duration and amount of reflux, and/or an inability to clear refluxed content can lead to gastroesophageal reflux disease (GERD). [3][4][5][6] Since the advent of high-resolution manometry (HRM), enhanced recognition of esophageal body motor patterns and esophagogastric junction (EGJ) morphology has improved our understanding of the relationship between motor abnormalities and gastroesophageal reflux disease (GERD). [3][4][5][6] Since the advent of high-resolution manometry (HRM), enhanced recognition of esophageal body motor patterns and esophagogastric junction (EGJ) morphology has improved our understanding of the relationship between motor abnormalities and gastroesophageal reflux disease (GERD).…”
Section: Introductionmentioning
confidence: 99%